Toksisitas Hematologi Regimen TAC (Docetaxel-Doksorubisin-Siklofosfamid) dan FAC (Fluorourasil-Doksorubisin-Siklofosfamid) pada Pasien Kanker Payudara di Rumah Sakit Kanker âDharmaisâ Jakarta: Analisis Data Rekam Medik 2007-2008 - Regimen, Toksisitas Hematologi; ANDRAJATI, RETNOSARI; ANDALUSIA, RIZKA (Indonesian Journal of Cancer, 2010)
Breast cancer in Indonesia the second most common cancer in women after cervical cancer in 2008. FAC and TAC are chemotherapy regiments for breast cancer that give good therapy response but affect patient haematology. Study about hematologic toxicity of TAC and FAC in breast cancer patient has not been conducted in âDharmaisâ Cancer Hospital. The purpose of this study was to determine hematologic toxicity of 6 cycles TAC (docetaxel 75 mg/m2, doxorubicin 50 mg/m2 and cyclophosphamide 500 mg/m2, day 1, 21) and FAC (fluorouracil 500 mg/m2, doxorubicin 50 mg/m2 and cyclophosphamide 500 mg/m2, day 1, 21) in breast cancer patients in âDharmaisâ Cancer Hospital. This study used cross sectional design in 11 and 179 patient medical records that were indentified treated with TAC and FAC. Patients received first cycles both regiments in 2007-2008. All stages of breast cancer were included in this study. Differences between TAC and FAC in proportion of haematology count after chemotherapy and average decrease of hematology count were analyzed by chi square and t test statistic methods. From 66 hematology data in patients treated with 6 cycles TAC grade 1-4 of hematologic toxicity occurred 84,8% in haemoglobin with average decrease 0,71 g/dl; 97% in leucocyte with average decrease 7,51 x 103 cell/?l; 22,7% in trombocyte with average decrease 147,77 x 103 cell/mm3. From 1079 hematology data in patients treated with 6 cycles FAC grade 1-4 of hematologic toxicity occurred 72,6% in haemoglobin with average decrease 0,66 g/dl; 85% in leucocyte with average decrease 2,73 x 103 cell/?l; and 10,9% in thrombocyte with average decrease 104,25 x 103 cell/mm3.